Comparison Between The Effects of Betamethasone Gel And Lidocaine Jelly To Reduce PostOperative Tracheal Tube Related Airway Symptoms - Alam, Syed Sajjad; Abbas, Nighat; Asghar, Ali; Rafique, Muhammad; Abid, Khadijah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the role of betamethasone gel and lidocaine jelly on reducing the post-operative airway complications related to tracheal tube.Study Design: Comparative prospective study.Place and Duration of Study: Department of Anesthesia, Liaquat National Hospital, from Jul 2019 to Jan 2020.Methodology: A total of 150 patients were randomly assigned into three different groups; group-B (0.05% betamethasone gel), group-L (tube lubricated with 2% lidocaine jelly) and group-C (intubated with un-lubricated tubes). Patients were assigned by using lottery method, which was carried out by a research assistant who was not involved in the study. There were 50 patients in each group.Results: Post-operative sore throat and post-extubation cough at 24-hours were statistically insignificant (p>0.05) between groups while hoarseness of voice at 24-hours postoperatively was significant (p